EKSISTENSI PRINSIP PENCEMAR MEMBAYAR DALAM SISTEM PENEGAKAN HUKUM AGRARIA - Sugianto, Fajar; Agustian, Sanggup Leonard; Basti, Nisa Permata (TANJUNGPURA LAW JOURNAL, 2020)
Law Number 32 of 2009 concern about Environmental Protection and Management does not provide adequate regulation in providing sanctions against perpetrators of pollution, except only providing a legal basis for employers to provide compensation payments to victims of pollution. Therefore it is necessary to know about the position of the Polluter Pays Principle in the Environmental Legal System as Agrarian Reform. The principle of paying polluters who have the function of authorizing should not be formulated in the explanatory section of the article. If following the explanation of Law No. 23 of 1997 concerning Environmental Management, the purpose of the principle of polluter pays, even has many meanings such as paying to pollute or can be interpreted as a license to pollute. As a result of the study of international law, the principle of polluter pays has two meanings, namely as an economic instrument with the intention of charging fees to potential polluters and is also interpreted as a basic instrument to hold legal liability for incidents of environmental pollution.Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup tidak memberikan pengaturan memadai dalam memberikan sanksi terhadap pelaku pencemaran, kecuali hanya memberikan landasan hukum bagi pengusaha untuk memberikan pembayaran kompensasi kepada korban pencemaran. Oleh karena itu perlu mengetahui mengenai kedudukan Prinsip Pencemar Membayar (Polluter Pays Principle) dalam Sistem Hukum Lingkungan Sebagai Reformasi Agraria. Prinsip Pencemar Membayar yang memiliki fungsi mengesahkan seharusnya tidak dirumuskan dalam bagian penjelasan pasal. Jika mengikuti penjelasan Undang-undang No. 23 Tahun 1997 tentang Pengelolaan Lingkungan Hidup, maka maksud Prinsip Pencemar Membayar, bahkan memiliki banyak pemaknaan seperti membayar untuk mencemari (paying to pollute) atau dapat dimaknai sebagai license to pollute. Hasil telaah hukum internasional, prinsip pencemar membayar memiliki dua pemaknaan, yaitu sebagai instrumen ekonomi dengan maksud pembebanan biaya kepada pelaku pencemar yang potensial dan diartikan juga sebagai instrument dasar untuk menuntut pertanggungjawaban hukum atas terjadinya kasus pencemaran lingkungan.